CAPITAL PRODUCTIVITY IN INDUSTRIALISED ECONOMIES: EVIDENCE FROM ERROR-CORRECTION MODEL AND LAGRANGE MULTIPLIER TESTS - D. Trofimov, Ivan (Economic Annals, 2017)
The paper re-examines the “stylized facts” of the balanced growth in developed economies, looking specifically at capital productivity variable. The economic data is obtained from European Commission AMECO database, spanning 1961-2014 period. For a sample of 22 OECD economies, the paper applies univariate LM unit root tests with one or two structural breaks, and estimates error-correction and linear trend models with breaks. It is shown that diverse statistical patterns were present across economies and overall mixed evidence is provided as to the stability of capital productivity and balanced growth in general. Specifically, both upward and downward trends in capital productivity were present, while in several economies mean reversion and random walk patterns were observed. The data and results were largely in line with major theoretical explanations pertaining to capital productivity. With regard to determinants of the capital productivity movements, the structure of capital stock and the prices of capital goods were likely most salient.